Clinical and Ultrasonographic Assessment of Nail Psoriasis: A Comprehensive Study - Maria Esposito; Lina Maria Magnanimi; Paolo Antonetti; Andrea De Berardinis; Cristina Pellegrini; Emanuele Vagnozzi; Manfredo Bruni; Camilla Gianneramo; Paola Cipriani; Maria Concetta Fargnoli; Antonio Barile; Piero Ruscitti (Dermatology Practical & Conceptual)
Introduction: In patients with plaque type psoriasis (PSO), the progression to psoriatic arthritis (PsA) exacerbates the disease's impact and increases disability risk. Nail psoriasis (NP) affects up to 90% of PSO patients with a wide spectrum of clinical features and is a significant predictor of enthesitis, often associated with early PsA stages.